PENGARUH KUALITAS PRODUK DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN HANDPHONE SAMSUNG ANDROID (Studi Pada Masyarakat Kota Unaaha Kab. Konawe) - Fitria (Jurnal Manajemen Lakidende: Economic & Business, 2019)
This study aims to determine the effect Partial Simultaneous and product quality and brand image of the Samsung brand mobile phone purchasing decisions Android community Konawe Unaaha City. The data collection is done with the interview. Documentation and Questionnaire on Urban Community Unaaha District. The study population was Unaaha District Urban Community and the sample size is 70 people. The analysis technique used is multiple linear regression using hypothesis testing, the F test and t test. The results of this study suggest that the independent variable (product quality and brand image simultaneously significant effect on purchasing decisions, this means that the better the quality of products offered and the better the brand image of Samsung, the higher the level of Consumer Purchase Decision. Based on the partial test (t test) variable product quality, and no significant negative influence on purchasing decisions, this means that the quality of products offered by Samsung does not affect the level of consumer purchase decision. Brand image and variable positive and significant influence on purchasing decisions, this means that the Samsung brand image affects the level of consumer purchase decision against Samsung products. The better the brand image of Samsung, the level of consumer purchase decisions increases, this study were obtained value of adjusted R square of 0.210, it means that 21% of purchasing decisions can be explained by the variable quality and brand image, while the remaining 79% of purchase decisions are influenced byaotheravariablesanotaexaminedainathisastudy.